2,4,6- Ttrichloroanisol:a consumer panel evaluation - Teixeira, Margarida I. V (2006)
“Cork taint” is a major problem in wine industry and is caused by contamination of wines. This contamination is usually attributed to wine cork stoppers and 2,4,6-trichloroanisole (2,4,6-TCA) is one of the compounds mostly associated to this off-flavour. In this work, a consumer panel performed “forced choice” triangular tests in order to measure Odour Detection Thresholds (ODT) and Taste Detection Thresholds (TDT) of 2,4,6-TCA in water, hydro-alcoholic solutions (11.5% and 18% ethanol) and white and red wines. A paired preference test was also performed by the panel in order to measure Odour Rejection Threshold (ORT) in white and red wine spiked with 2,4,6-TCA. Results obtained show that the ODT and the TDT for 2,4,6-TCA in water were 0.2 and 0.3 ng/L, respectively. In hydro-alcoholic solutions with 11.5% and 18% ethanol the ODT were 4 and 10 ng/L respectively. In red wine the ODT and the TDT were 0.9 and 1.7 ng/L and in white wine were 1.5 and 1.0 ng/L respectively. ORT for white was 10.4 ng/L and for red wines 16.0 ng/L. These results suggest that although this group of consumers detected very low concentrations of 2,4,6-TCA in wines, they did not reject the wine at these low concentration values.